2008
DOI: 10.1007/s10620-007-0143-4
|View full text |Cite
|
Sign up to set email alerts
|

Serrated Adenoma is a Risk Factor for Subsequent Adenomatous Polyps

Abstract: While SA are uncommon, they are commonly associated with colorectal cancer. Serrated adenomas appear to be found more commonly in the left colon and in older patients. This study found a significant association between SA and the subsequent development of adenomatous polyps. Further studies are needed to define appropriate preventive strategies for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…A total of 68 English language abstracts that involved human subjects were retrieved, and 28 potentially relevant studies were reviewed ( 10,(11)(12)(13). Aft er exclusion of 15 studies that did not report the information of interest ( 12,21,(23)(24)(25)(28)(29)(30)32,33,(35)(36)(37)(38)(39) and 4 studies that had insuffi cient data for meta-analysis ( 13,22,31,41 ), our fi nal analysis included nine studies published between 2009 and 2014.…”
Section: Search Resultsmentioning
confidence: 99%
“…A total of 68 English language abstracts that involved human subjects were retrieved, and 28 potentially relevant studies were reviewed ( 10,(11)(12)(13). Aft er exclusion of 15 studies that did not report the information of interest ( 12,21,(23)(24)(25)(28)(29)(30)32,33,(35)(36)(37)(38)(39) and 4 studies that had insuffi cient data for meta-analysis ( 13,22,31,41 ), our fi nal analysis included nine studies published between 2009 and 2014.…”
Section: Search Resultsmentioning
confidence: 99%
“…A small case-control study including 17 patients with SA and 17 controls found that the finding of an SA at baseline colonoscopy was associated with adenomatous polyps in subsequent examinations (24% vs 0%; P=0.01) [12]. • The presence of a proximal ND-SP and no neoplasia on index colonoscopy is associated with an increased risk of any adenoma during surveillance (OR, 3.14; 95% CI, 1.59-6.2)…”
Section: Risk Of Colorectal Cancer In Serrated Polypsmentioning
confidence: 99%
“…The incidence of cancerous transformation of serrated polyps remains unknown and the hypothesis that the presence of serrated polyps constitutes a risk factor for CRC has been based on small studies until very recently ( Table 2) [12][13][14]46]. The first report showing a correlation between serrated polyps and development of adenomatous polyps in a large cohort was published in 2009 by Li et al [47].…”
Section: Risk Of Colorectal Cancer In Serrated Polypsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leur implication est égale-ment démontrée pour les PFS proximaux, avec un RR de CCR plus marqué pour les PFS larges et proximaux (5,4 [2,4-10,1]) [37] ou de 3,4 (IC 95 % : [1,7]) pour les néoplasies avancées [38]. Cette dernière étude a surtout montré une augmentation plus marquée du risque de récidive de néoplasie (3,1 ; IC 95 % : [1,6-6,2]) ou de néoplasie avancée (2,2 ; IC 95 % : [1,01-4,6]) à 5,5 ans en présence de PFS à localisation proximale, alors que ce risque était déjà connu pour les PFT du côlon gauche [39].…”
Section: Cas Des Polypes Festonnés (Pf) Ou Dentelésunclassified